2020
DOI: 10.1128/msphere.00409-20
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Regulated by the LPS/TLR2 Immune Axis as Bona Fide Biomarkers for Diagnosis of Acute Leptospirosis

Abstract: Leptospirosis remains a significant human health issue due to its systemic complications. Therefore, biomarkers that are more effective are urgently needed for the early diagnosis of leptospirosis. MicroRNAs (miRNAs) are evolutionarily conserved regulatory RNAs that have shown the potential to be used as biomarkers for diagnosis, prognosis, and therapy of infectious diseases. In this study, we performed an unbiased screen using the miRNome miRNA array to identify circulating miRNAs with the potential to serve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…In fact, miR-let-7b-5p research is very limited currently; however, some scholars have noticed its role in infection and inflammation [ 28 , 29 ]. Our study also suggests that miR-let-7b-5p can participate in the antibacterial process, through the STAT1 pathway ( Figure 5(e) ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, miR-let-7b-5p research is very limited currently; however, some scholars have noticed its role in infection and inflammation [ 28 , 29 ]. Our study also suggests that miR-let-7b-5p can participate in the antibacterial process, through the STAT1 pathway ( Figure 5(e) ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding leptospirosis, in vitro data demonstrated that several miRNAs associated with immune regulation were involved in Leptospira infection in a virulence- and species-specific manner [ 20 ]. Moreover, a previous study identified specific miRNAs that were able to discriminate the infection from other acute febrile diseases with a high sensitivity and specificity [ 21 ]. Additionally, our group recently demonstrated distinct expression of circulating microRNAs as novel biomarkers for identifying severe leptospirosis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…NFκB [48], Fibronectin [30] and CXCL2/MIP2 [40] showed the inhibition or decreased level in TLR2 blocked/deficient cell lines. The data convey the involvement of TLR2 in triggering the immune response during the Leptospira infection.…”
Section: Tlr2 Response In In-vitro and Ex-vivo Studiesmentioning
confidence: 92%
“…The studies encompassed a range of experimental models, including 3 human [20][21][22], 5 in-vivo [23][24][25][26][27], 14 in-vitro [28][29][30][31][32][33][34][35][36][37][38][39][40][41], and 3 ex-vivo studies [42][43][44]. Additionally, four studies [9,10,45,46] used a combination of in-vivo and in-vitro models, while two studies [47,48] used a combination of human, in-vitro, and in-vivo models. Finally, one study [49] used both in-vivo and ex-vivo models.…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation